GE_GERICHTE P/29709/2024 vom 24. April 2025 - GE Cour de justice (2025)
DÉLAI;ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;CONTRAINTE(DROIT PÉNAL);LÉSION CORPORELLE;VOIES DE FAIT | CPP.310.al1; CP.181; CP.31; CP.123.al1; CP.126.al1